Magnetic Resonance Imaging Detects Chronic Rhinosinusitis in Infants and Preschool Children with Cystic Fibrosis - Sommerburg, Olaf; Wielpütz, Mark O.; Trame, Jan-Philipp; Wuennemann, Felix; Opdazaite, Elzbieta; Stahl, Mirjam; Puderbach, Michael U.; Kopp-Schneider, Annette; Fritzsching, Eva; Kauczor, Hans-Ulrich; Baumann, Ingo; Mall, Marcus A.; et al. (Annals of the American Thoracic Society, 2020)
Chronic rhinosinusitis (CRS) contributes to disease burden of patients with cystic fibrosis (CF). However, its onset and progression in infants and preschool children with CF remain poorly understood. To determine the prevalence and extent of CRS in young children with CF using magnetic resonance imaging (MRI). MRI was performed in sedation in 67 infants and preschool children with CF (mean age 2.3 ± 2.1 yr; range 0-6 yr) and 30 non-CF control subjects (3.5 ± 2.0 yr; range 0-6 yr). Paranasal sinus dimensions and structural abnormalities, including mucosal swelling; mucopyoceles; and nasal polyps of the maxillary, frontal, sphenoid, and ethmoid sinuses; and, in addition, medial maxillary sinus wall deformation, were assessed using a dedicated CRS MRI scoring system. Pneumatization and dimensions of paranasal sinuses did not differ between the two groups. MRI detected an increased prevalence of mucosal swelling (83% vs. 17%;